Influence of the quality of remuneration committee and organizational factors on management compensation plan design and performance - Mehrabanpoor, Mohammadreza (2012)
During the last two decades, numerous studies have focused on the relationships between management compensation, corporate governance and firm performance. Studies on the design of management compensation plan and its effects on firm performance are related to those on agency problems arising primarily from the separation of ownership and control and the misaligned incentives between managers and shareholders. The misalignment of management incentives could lead to dysfunctional behaviour that could affect firm value adversely. Hence, a proper design of management compensation plan is crucial to resolve the manager– shareholder agency conflicts. This study examines the relationships between a certain corporate governance related mechanism and organisational factors and management compensation plan design,and how performance-based management compensation affects firm performance. The examined corporate governance mechanism is the quality of remuneration committee, and organisational factors are composed of ownership structure, and firm leverage. In the main market of Bursa Malaysia, 207 out of 828 companies in different industry sectors from 2008 to 2010 were randomly selected as a sample. This constituted 25 percent of the total listed companies which comprise more than 56 percent of total market capitalisation. The data for performance-based management compensation, the quality of remuneration committee, and ownership structure were collected from the annual financial reports of the sample companies. The data of firm performance, and firm leverage were obtained from Standard and Poor’s Capital IQ database. The data were analysed using the regression model.Moreover, the Baron and Kenny (1986) procedure improved by Mathieu and Taylor (2006) was used in order to test the mediating model. Newey-West heteroskedasticity and autocorrelation consistent (HAC) Standard Errors and Covariance were used for the estimation of the ordinary least squares (OLS) regression. Ownership structure variable was represented by four dummy variables, while the other variables were measured as ratio scale. Since senior management compensation constitutes a major component of a firm’s total incentive payment, this study on performance-based management compensation helps to evaluate the effectiveness of certain corporate governance related mechanisms in Malaysia. The results of this study have shown that: First, the quality of remuneration committee is found to have a moderately significant positive impact on performance-based management compensation in Malaysian listed companies. This study measures the quality of remuneration committee based on six comprehensive categories with twenty six dimensions. The quality of the remuneration committee is a key factor in enhancing the effectiveness of management compensation plan design. Second, four different types of ownership structure i.e. family ownership, GLC ownership, institutional ownership and dispersed ownership are found to have significant negative impact on performance-based management compensation. These results are consistent with the literature findings; although the finding related to institutional ownership is contrary to expectation. Third, firm leverage is found to have a significant negative effect on performancebased management compensation. This is because high leverage results in higher monitoring. Thus, the high monitoring cost negatively impacted management compensation and performance. Fourth, performance-based management compensation is found to have a significant positive impact on firm financial performance. Effective and performance-based management compensation plan design aligns interest of managers with those of shareholders. Fifth, among the four different types of ownership, institutional and dispersed ownership have significant negative impact on firm performance, whilst family and GLC ownership have moderately significant negative effect on firm performance. Firm leverage is found to have a significant negative effect on firm performance. Finally, performance-based management compensation does not mediate the quality of remuneration committee-performance, dispersed ownership-performance and firm leverage-performance relationships, but it fully mediates family ownershipperformance,GLC ownership-performance, and institutional ownership-performance relationships. Overall, the results of this study indicate that corporate governance related factors such as the quality of remuneration committee, and organisational factors such as ownership structure and firm leverage have a significant influence on the design of management compensation plan, which in turn affects firm performance. Finally, performance-based management compensation mediates the relationship between ownership structure and firm performance. The results of this study show that it is the quality of the remuneration committee rather than the existence of the committee that matters. This research empirically explores aspects of remuneration committee and performance-based management compensation that have, hitherto, not been much examined in the existing literature,especially in developing countries. The majority of reform efforts try to improve transparency and disclosure in the paysetting processes and internal control. However, a little attention gave to the quality of remuneration committee and its potential to discipline the behaviour of the executives. If agency problems are to be sufficiently mitigated via the incentive compensation, then policy makers may have to focus their attention to how the remuneration packages are formulated.